Human Genome Project- A Review (Medicine Today, 2014)
Biotechnology and genetic engineering has advanced medical science so that we are now blessed with treatments of numerous diseases with the gene therapy. Mapping and sequencing of human genome was started in 1989 and ended in 2003. The genome project aimed to find out the function of every gene in human body and replace any gene that is mutated and causes disease. This is a review of the process by which the actual sequencing was done. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21315 Medicine Today 2014 Vol.26(1): 53-55